The Effect of Mobile Application-Delivered Intervention on Social Media Addiction Among Adolescents in Indonesia - Benny Novico Zani; Faridah Mohd Said; Nisha Nambiar; Siti Sholihat (Journal of World Future Medicine, Health and Nursing, 2024)
Developments in the field of technology are increasingly rapid in this millennial era makes it easy for everyone to socialize with other people from various parts of the world through a link site known as the media social. The general objective of this study is to examine the effect of mobile application on mental health among adolescents in Depok, Indonesia. Experimental design is research used to find the effect of certain treatments on others under controlled conditions. The target population in this study were adolescents aged 15-18 years, and studied in senior high school students. The social media Safe App (bilingual: Indonesia-English language) was developed as a mobile app. The instrument used in this study was DASS-21 scale. The difference between the intervention group and the control group in terms of the average scores on mental health in the control group and in the intervention, group was determined using a bivariate analysis with a paired t-test. Of 200 adolescents in the intervention group, the mean age was 16.37 (SD+2.55), 60% male, and (60%) of them used internet as a source of information. While, in the control group their mean age was 16.34 (SD=2.39), 58.5% male, and 55% of them used internet as a source of information. In the intervention group, DASS score was significantly decreased 5.26 times before intervention and after one month intervention (post-test), with pvalue=0.000. While in the control group, no significant decreased on a total score of DASS (pvalue>0.05. The results of this study can be used as a reference for other researchers who will develop research on the impact of social media use on mental health disorders. Developing a mobile application or website to measure the level of addiction on social media with usage notifications that exceed the safe duration of social media use to limit the intensity of social media use time as a preventive tool against mental health disorders.